2018
DOI: 10.5194/wes-3-163-2018
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of subcomponent over full-scale blade testing elaborated on a trailing-edge bond line design validation

Abstract: Abstract. Wind turbine rotor blades are designed and certified according to the current IEC (2012) (International Electrotechnical Commission) and DNV GL AS (2015) (Det Norske Veritas Germanischer Lloyd Aksjeselskap) standards, which include the final full-scale experiment. The experiment is used to validate the assumptions made in the design models. In this work the drawbacks of traditional static and fatigue full-scale testing are elaborated, i.e., the replication of realistic loading and structural response… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
(24 reference statements)
0
14
0
Order By: Relevance
“…Typical failure modes observed in full-scale blade tests includes adhesive joint debonding, sandwich core failure and composite laminate failure. In recent years, subcomponent testing has been used [6][7][8][9][10] to understand the structural behavior of critical parts of composite blades. The subcomponent testing could be an important complement to the full-scale blade tests that are mandatory for certification of wind turbine blades.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Typical failure modes observed in full-scale blade tests includes adhesive joint debonding, sandwich core failure and composite laminate failure. In recent years, subcomponent testing has been used [6][7][8][9][10] to understand the structural behavior of critical parts of composite blades. The subcomponent testing could be an important complement to the full-scale blade tests that are mandatory for certification of wind turbine blades.…”
Section: Introductionmentioning
confidence: 99%
“…The subcomponent testing could be an important complement to the full-scale blade tests that are mandatory for certification of wind turbine blades. Regarding the subcomponents of trailing edges, efforts have been made to elaborate benefits of subcomponent over full-scale testing [8] and comparing different subcomponent test concepts [9]. Recent work [11] has assessed the failure of trailing edge subcomponents by addressing structural instability associated with pre-buckling and post-buckling response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basis for establishing the test loads is the entire envelope of blade design loads. The full‐scale testing does not necessarily cover all critical loading conditions along the blade length as they would occur in the field, for example, in a trailing edge bond line under combined flap‐wise and lead‐lag loading. Moreover, some transient loads such as impact during transportation and installation cannot be simulated in the full‐scale test, but they may cause local damage in the blade.…”
Section: Introductionmentioning
confidence: 99%
“…flapwise and lead-lag. A drawback of these unidirectional tests is that the loads introduced into the blade do not necessarily represent the loading the blade will experience under field conditions as Rosemeier et al (2018) have shown.…”
Section: Introductionmentioning
confidence: 99%